WHITE MATTER CONNECTIVITY CHANGES DUE TO CEREBRAL MICROHEMORRHAGES IN GERIATRIC MILD TRAUMATIC BRAIN INJURY. (11th November 2018) - Irimia, A; Rostowsky, K; Chowdhury, N; Maher, A
Abstract: Recent studies utilizing susceptibility-weighted imaging (SWI) suggest a higher incidence of cerebral microbleeds (CMBs) in geriatric patients with mild traumatic brain injury (mTBI) compared to mTBI victims in the second, third and fourth decades of life. The clinical implications of acute CMB findings on neuroradiological examinations remain unclear, partly because older adults' TBI-related CMBs can be difficult to distinguish non-invasively from CMBs associated with other conditions, including cerebral amyloid angiopathy (CAA). In this longitudinal study, we combined magnetic resonance and diffusion tensor imaging (MRI and DTI, respectively) to assess the nature and extent of white matter (WM) connectivity alterations due to CMBs after mTBI. A total of 26 geriatric mTBI victims were scanned both acutely (<7 days after injury) and chronically (6 months after injury) and their structural connectomes were reconstructed and analyzed using graph-theoretic techniques. Preliminary evidence suggests that (A) mTBI-related CMBs can be associated with brain circuitry changes affecting peri-lesional WM integrity, and that (B) WM fiber bundles passing through the vicinity of CMBs can exhibit substantial structural alterations even relatively far from the CMBs themselves. Specifically, six months post-injury, 21 participants were found to exhibit significant alterations (p < 0.001) in mean diffusivity along 47% (σ = 21%) of their perilesional WM bundles. This study points to the usefulness of connectomic analysis to investigate CMB-related WM alterations and suggests that SWI MRI should be used in future studies to clarify how CMBs affect geriatric mTBI patients.